2023
DOI: 10.1111/1365-2664.14462
|View full text |Cite
|
Sign up to set email alerts
|

Large‐scale changes in macrobenthic biodiversity driven by mangrove afforestation

Abstract: Large‐scale anthropogenic mangroves have been constructed in coastal regions worldwide but our understanding of their ecological effects is limited. In particular, the question of whether and how anthropogenic mangroves influence biodiversity patterns remains elusive. Here, we investigated the influence of large‐scale anthropogenic mangroves on biodiversity patterns of mangrove macrobenthos. Specifically, we measure and seek to explain differences in species richness, abundance, assemblage composition and dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 119 publications
0
3
0
Order By: Relevance
“…This indicated that deterministic processes are more important than stochastic processes in shaping the macrobenthos communities under both artificial and natural restoration. Artificial restoration sites had severe human interference, which made the macrobenthos communities sensitive to environmental changes induced by human activities (Chen et al., 2023 ). Although there is less human disturbance in natural restoration sites, changed tidal and soil elements can impact the species composition and competition pattern of macrobenthic communities (Zhang et al., 2022 ), which determines the macrobenthic community assembly.…”
Section: Discussionmentioning
confidence: 99%
“…This indicated that deterministic processes are more important than stochastic processes in shaping the macrobenthos communities under both artificial and natural restoration. Artificial restoration sites had severe human interference, which made the macrobenthos communities sensitive to environmental changes induced by human activities (Chen et al., 2023 ). Although there is less human disturbance in natural restoration sites, changed tidal and soil elements can impact the species composition and competition pattern of macrobenthic communities (Zhang et al., 2022 ), which determines the macrobenthic community assembly.…”
Section: Discussionmentioning
confidence: 99%
“…Sea-level rise significantly influences the historical distribution of mangrove forests, leading to speciation in five common mangrove species via multiple cycles of mixing, isolation, and mixing ( Lovelock et al., 2015 ; He et al., 2022 ). Meanwhile, low temperature stress governs the latitudinal range limits for contemporary mangrove flora ( Lin, 1999 ) and plays a crucial role in mangrove afforestation and restoration ( Ellison, 2000 ; Quisthoudt et al., 2012 ; Su et al., 2021 ; Chen et al., 2023 ). Given the ecological importance of mangroves and the potential impact of climate change on their habitats, further research into their adaptation to low temperatures is vital.…”
Section: Introductionmentioning
confidence: 99%
“…The goals of afforestation, according to the existing conditions in an area, may include: stabilization of sand and deserti cation, wood production, improvement of soil conditions and characteristics, prevention of soil erosion, protection or creation of wildlife habitat, supply of fuel and animal feed and creation of windbreaks in soil conservation (Chen et al, 2023;Gbadebo, 2022;Lucas-Borja et al, 2022). To choose suitable tree and shrub species for establishing forests as plantations in dry areas, it is necessary to know the local site conditions, consider socioeconomic factors and be able to predict future growth and effects on soil resources.…”
Section: Introductionmentioning
confidence: 99%